Inhibition of virus attachment to CD4+ target cells is a major mechanism of T cell line-adapted HIV-1 neutralization. - Ugolini, S; Mondor, I; Parren, P; Burton, DR; Tilley, SA; Klasse, P; Sattentau, Q (1997)
Antibody-mediated neutralization of human immunodeficiency virus type-1 (HIV-1) is thought to function by at least two distinct mechanisms: inhibition of virus-receptor binding, and interference with events after binding, such as virus-cell membrane fusion. Here we show, by the use of a novel virus-cell binding assay, that soluble CD4 and monoclonal antibodies to all confirmed glycoprotein (gp)120 neutralizing epitopes, including the CD4 binding site and the V2 and V3 loops, inhibit the adsorption of two T cell line-adapted HIV-1 viruses to CD4+ cells. A correlation between the inhibition of virus binding and virus neutralization was observed for soluble CD4 and all anti-gp120 antibodies, indicating that this is a major mechanism of HIV neutralization. By contrast, antibodies specific for regions of gp120 other than the CD4 binding site showed little or no inhibition of either soluble gp120 binding to CD4+ cells or soluble CD4 binding to HIV-infected cells, implying that this effect is specific to the virion-cell interaction. However, inhibition of HIV-1 attachment to cells is not a universal mechanism of neutralization, since an anti-gp41 antibody did not inhibit virus-cell binding at neutralizing concentrations, implying activity after virus-cell binding.